EMPOWERMENT OF ERGONOMIC FERTILIZER SOWING EQUIPMENT INNOVATION IN FARMER GROUPS TO INCREASE PRODUCTIVITY AND EFFECTIVENESS IN AGRICULTURE AND TEMPEH WASTE MANAGEMENT IN SADASARI VILLAGE - Jajang Rahmatudin; Mega Rizky Molidina; Lily Tira Depuri; Ida Kusumawati; Nur Farhanah Sholihah; Nur Azizah; Ibnu Alwan; Jihan Nurfadhila; Deta Arella Paramita; Maulana Aditya Rahman; Nazla Fadhilah; Lusi Shofiatul Maula; Denis Setiawan Fahreza; Syaiful Rahmatullah; Rifal Ristianto; Iswadi Iswadi; Ita Setiawati; Ferdy Nur Adhiansyah; Maulana Akbar (Ann Publisher, 2026)
Background. The Student Work Lecture Program (KKM), held in Sadasari Village, Argapura District, Majalengka Regency, aims to address two main problems faced by the local community. The first problem is the low work efficiency of farmers, who still use traditional fertilizer-sowing tools that are not ergonomic, leading to physical fatigue and reduced agricultural productivity. The second problem is environmental pollution from liquid waste from tempeh production, which is directly discharged into rivers and irrigation canals, even though the waste has significant economic potential if processed properly. Purpose. To overcome these problems, the KKM team developed two innovative solutions, namely designing an ergonomic fertilizer sowing tool made of PVC and durable materials that are lighter and easier to use, and processing tempeh liquid waste into Liquid Organic Fertilizer (POC) using simple materials such as tempeh waste, EM4, and molasses. Method. This program is carried out through five systematic stages starting from preparation, problem identification, innovation design, implementation through socialization and practical training to farmer groups and MSME actors, to program evaluation. The socialization activity also involved the Argapura District Agricultural Extension Center (BPP) in providing additional materials and ensuring the sustainability of the program. Results. The results of this program include increased knowledge and skills among the community in using appropriate technology for agriculture, as well as new skills in processing waste into products of economic value. Conclusion. This program has not only reduced environmental pollution but also opened new business opportunities for the people of Sadasari Village. With a participatory approach that actively involves the community in every stage. Implementation. This KKM program is expected to be sustainable, have a long-term positive impact on the welfare of village communities, and serve as a model that can be replicated in other villages with similar problems.